Effect of autologous dendritic cell cytokine-induced killer on refractory metastatic colorectal cancer: a matched case–control comparative study - Chang, Sheng-Chi; Ke, Tao-Wei; Chen, William Tzu-Liang; Shyu, Weoi-Cherng; Jeng, Long-Bin (Frontiers in Immunology, 2024)
Background Patients with metastatic colorectal cancer (mCRC) who are refractory to two or more lines of systemic chemotherapy have limited therapeutic options. The aim of this study was to evaluate the effect of autologous dendritic cell cytokine-induced killer (DC-CIK) transfer on the survival of patients with mCRC who are refractory or intolerant to at least two lines of systemic chemotherapies. Methods A matched case–control comparative study was conducted with patients who received DC-CIK immunotherapy in addition to standard chemotherapy (cases) and those with standard chemotherapy alone (controls). The primary objective was to compare the duration of oncologic survival, including overall survival (OS) and progression-free survival (PFS), between the two groups. Results A total of 27 cases and 27 controls were included. The median OS in the DC-CIK case group was 18.73 ± 5.48 months, which was significantly longer than that in the control group (14.23 ± 1.90 months, p = 0.045). However, there was no significant difference in PFS between the two groups (p = 0.086). Subgroup analysis showed that in patients with liver or extra-regional lymph node metastasis, DC-CIK cases had longer OS than controls (17.0 vs. 11.87 months, p = 0.019; not match vs. 6.93 months, p = 0.002, respectively). In patients with Eastern Cooperative Oncology Group (ECOG) scale 0 or wild RAS/BRAF, DC-CIK cases showed a significant increase in OS duration compared to controls (28.03 vs. 14.53 months, p = 0.038; 18.73 vs. 11.87 months, p = 0.013, respectively). Conclusions The addition of autologous DC-CIK to standard chemotherapy had a positive effect on OS of patients with refractory mCRC, especially those with liver or extra-regional lymph node metastasis, ECOG = 0, and wild RAS/BRAF status.